Novel biomarkers with promising benefits for diagnosis of cervical neoplasia: a systematic review - Onyango, Calleb George (Infect Agent Cancer, 2020)
BACKGROUND: Cervical cancer screening is slowly transitioning from Pappanicolaou cytologic screening to primary Visual Inspection with Acetic Acid (VIA) or HPV testing as an effort to enhance early detection and treatment. However, an effective triage tests needed to decide who among the VIA or HPV positive women should receive further diagnostic evaluation to avoid unnecessary colposcopy referrals is still lacking. Evidence from experimental studies have shown potential usefulness of Squamous Cell Carcinoma Antigen (SCC Ag), Macrophage Colony Stimulating Factor (M-CSF), Vascular Endothelial Growth Factor (VEGF), MicroRNA, p16INKa / ki-67, HPV E6/E7/mRNA, and DNA methylation biomarkers in detecting premalignant cervical neoplasia. Given the variation in performance, and scanty review studies in this field, this systematic review described the diagnostic performance of some selected assays to detect high-grade cervical intraepithelial neoplasia (CIN2+) with histology as gold standard. METHODS: We systematically searched articles published in English between 2012 and 2020 using key words from PubMed/Medline and SCOPUS with two reviewers assessing study eligibility, and risk of bias. We performed a descriptive presentation of the performance of each of the selected assays for the detection of CIN2 + . RESULTS: Out of 298 citations retrieved, 58 articles were included. Participants with cervical histology yielded CIN2+ proportion range of 13.7–88.4%. The diagnostic performance of the assays to detect CIN2+ was; 1) SCC-Ag: range sensitivity of 78.6–81.2%, specificity 74–100%. 2) M-CSF: sensitivity of 68–87.7%, specificity 64.7–94% 3) VEGF: sensitivity of 56–83.5%, specificity 74.6–96%. 4) MicroRNA: sensitivity of 52.9–67.3%, specificity 76.4–94.4%. 5) p16INKa / ki-67: sensitivity of 50–100%, specificity 39–90.4%. 6) HPV E6/E7/mRNA: sensitivity of 65–100%, specificity 42.7–90.2%, and 7) DNA methylation: sensitivity of 59.7–92.9%, specificity 67–98%. CONCLUSION: Overall, the reported test performance and the receiving operating characteristics curves implies that implementation of p16ink4a/ki-67 assay as a triage for HPV positive women to be used at one visit with subsequent cryotherapy treatment is feasible. For the rest of assays, more robust clinical translation studies with larger consecutive cohorts of women participants is recommended. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13027-020-00335-2.